Hello.
-7h + 2(-4h + 5) > -4h + 1 + 10 ; solve for h
Our first step is to get rid of all the parenthesis. We can do this by simplifying everything out.
-7h - 8h + 10 > -4h + 11
Add like terms.
-15h + 10 > -4h + 11
Now, we must isolate our variables. We do this by moving all variables to one side and moving our other numbers to the other.
Subtract 10 from both sides. Then, add 4h to both sides.
-15h + 4h > 11 - 10
Simplify.
-h > 1
Divide both sides by -1.
However, keep in mind that when dividing with a negative, you must change the sign. Therefore, > turns into <
-h ÷ -1 < 1 ÷ -1
h < -1
Answer:
The side length is multiplied by ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Step-by-step explanation:
we know that
The area of the original square is equal to
![A=9^{2}=81\ in^{2}](https://tex.z-dn.net/?f=A%3D9%5E%7B2%7D%3D81%5C%20in%5E%7B2%7D)
If the area is doubled
then
The area of the larger square is
![A1=(2)81=162\ in^{2}](https://tex.z-dn.net/?f=A1%3D%282%2981%3D162%5C%20in%5E%7B2%7D)
Remember that
If two figures are similar, then the ratio of its areas is equal to the scale factor squared
Let
z ----> the scale factor
x ----> the area of the larger square
y ---> the area of the original square
so
![z^{2}=\frac{x}{y}](https://tex.z-dn.net/?f=z%5E%7B2%7D%3D%5Cfrac%7Bx%7D%7By%7D)
we have
![x=162\ in\^{2}](https://tex.z-dn.net/?f=x%3D162%5C%20in%5C%5E%7B2%7D)
![y=81\ in\^{2}](https://tex.z-dn.net/?f=y%3D81%5C%20in%5C%5E%7B2%7D)
![z^{2}=\frac{162}{81}](https://tex.z-dn.net/?f=z%5E%7B2%7D%3D%5Cfrac%7B162%7D%7B81%7D)
![z^{2}=2](https://tex.z-dn.net/?f=z%5E%7B2%7D%3D2)
------> scale factor
therefore
The side length is multiplied by ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Answer:
Your answer is -2 hope this helps
Answer:
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Step-by-step explanation:
We have the equation ![x-1=-5-x](https://tex.z-dn.net/?f=x-1%3D-5-x)
In order to solve for x, we need to get all of the x's to one side and everything else to the opposite side
![x-1=-5-x](https://tex.z-dn.net/?f=x-1%3D-5-x)
First, we can add 1 to each side
![x=-4-x](https://tex.z-dn.net/?f=x%3D-4-x)
Now, we can add x to each side
![2x=-4](https://tex.z-dn.net/?f=2x%3D-4)
Next, we can divide each side by 2
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
And here is our answer.
You need to divide the miles by the hours to et the Average speed.
M divided by h = s
Because to get the mph (miles per hour) you multiply the average speed to the hours.
S•h=mph